Prediction of prospects in dance and gymnastic sports based on the method of assessing the structure of an individual somatotype - Druz, V.; Volkova, Y.; Huliaiev, O. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to determine the relationship between the motor, trophic and mental qualities of an athlete in accordance with the constitution of his somatotype in order to establish at an early stage of the morphofunctional development of objective, phylogenetically determined signs of motor talent for sports dancing.